2014
DOI: 10.1158/1940-6207.capr-13-0367
|View full text |Cite
|
Sign up to set email alerts
|

Benign Breast and Gynecologic Conditions, Reproductive and Hormonal Factors, and Risk of Thyroid Cancer

Abstract: The higher incidence of thyroid cancer in women compared to men suggests an influence of sex steroid hormones in the etiology of this malignancy. We investigated a comprehensive set of potential indicators of lifetime sex steroid hormone exposure in relation to thyroid cancer risk. Using data from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial, which enrolled 70,047 women, 50–78 years old, we prospectively examined associations of self-reported history of benign breast and gynecological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 48 publications
7
63
2
4
Order By: Relevance
“…Therefore, we defined the number of reproductive years in this study to assess the exposure of thyroid tissue to endogenous sex hormone more clearly. After adjusting for other variables, the number of reproductive years significantly increased the risk of thyroid cancer, consistent with results of a previous study of Melissa et al . Previous studies have shown that oestrogen can promote proliferation and metastasis of thyroid cancer cells .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we defined the number of reproductive years in this study to assess the exposure of thyroid tissue to endogenous sex hormone more clearly. After adjusting for other variables, the number of reproductive years significantly increased the risk of thyroid cancer, consistent with results of a previous study of Melissa et al . Previous studies have shown that oestrogen can promote proliferation and metastasis of thyroid cancer cells .…”
Section: Discussionsupporting
confidence: 90%
“…Third, pregnancy and parity showed the strongest associations with thyroid cancer. Several studies have shown that pregnancy and parity could increase the risk for thyroid cancer . In our study, pregnancy and parity significantly increased the risk thyroid cancer (Table ).…”
Section: Discussionsupporting
confidence: 64%
“…The strongest association was with a history of cervical intraepithelial neoplasia grade 3 (RR ¼ 4.03, 95% CI: 2.59-6.28), reflecting the importance of high-risk strains of human papilloma virus as causative agents of both cervical (Walboomers et al, 1999) example, as tubal ligation is usually performed for permanent contraception, it is likely to be more common among women who are sexually active, and who thus may be more likely to be exposed to sexually-transmitted infections, such as human papilloma virus, and the consequent increased risk of anal cancer. There have been reports on possible relationships between tubal ligation and other cancers, including possible reductions in risk of colorectal (Cape and Kreiger, 1999;Rosenblatt et al, 2004) and stomach cancer (Dorjgochoo et al, 2009), and increased risks of thyroid cancer (Braganza et al, 2014) and lymphatic and haematopoietic malignancies (Kjaer et al, 2004). We did not replicate any of these findings.…”
Section: Discussioncontrasting
confidence: 55%
“…Hysterectomy is one of the most common surgical procedures in gynaecology worldwide and is mainly performed in case of a benign disease such as fibroma and endometriosis, conditions which are associated with lifetime sex steroid hormone exposure …”
Section: Introductionmentioning
confidence: 99%